Reporte De Caso Urolitiasis Canina Durante La Pasantía En Clínica Veterinaria De Pequeños Animales (2023)
The internship is an opportunity that the university offers as a degree option. It serves as a method to complement students' learning and training in the practical area of ​​daily clinical practice, thus helping to strengthen skills and knowledge acquired in the academic field. It offers a space in which students integrate theoretical knowledge with practical experience. This internship was conducted at the veterinary clinic "El Bosque Animal - Clínica Veterinaria" located in Bogotá, Colombia, with a total of 250 practical hours. The clinic has different areas such as outpatient care, clinical laboratory, hospitalization, surgery, and imaging, allowing students to acquire multidisciplinary knowledge for their future careers.